Politics and Violence in Rancière: an implicit or intermittent link? (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
This work questions the relationship between politics and violence in Rancière. Considering his concepts of politics as a symbolic order and as that which lies beyond the State, it analyzes if this links politics to violence or not. It could be affirmed that Rancière does not thoroughly explore the theoretical richness of these two premises. For Rancière, violence seems to emanate only from the police in that they harm the equality of any two beings, as supposed from politics, which implies that violence is linked exclusively to the State, a paradigmatic place of the police. So, paradoxically, this flows with western tradition, in which politics was considered nonviolent because it promoted the good life, since for Rancière, politics remains far from anything violent because it is an activity that repairs the only violence, that of the State.